GIFTED PUPILS’ LEARNING LINKS - Brandisauskienė, Agnė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article aims at revealing the links of gifted pupils’ learning. Seeking to achieve the aim, a qualitative research, which involved 13 gifted learners of the first-second grades in secondary school, and quantitative research in learning environment have been conducted. The quantitative research was carried out employing What is Happening in the Classroom Questionnaire to survey gifted pupils (334 pupils). The research findings allow maintaining that gifted surface learning is more characteristic of gifted learning than deep learning, whereas the essence of learning compliant with the level of their abilities, interests and inclinations, is often unspecified. The learners with exceptional intellectual abilities tend to learn by using the techniques of memorisation; therefore, learning is rarely related to positive experiences. Moreover, the pupils’ inclination to surface learning is confirmed by the research into class environment: the majority of high school learners claim that they rarely discuss, express their opinion, ask questions or provide explanations of problem-solving in the classroom, i.e. they miss opportunities to actively construct own learning in the process of education.